Estimated Sweetness in US Diet Among Children and Adults Declined From 2001 to 2018: A Serial Cross-Sectional Surveillance Study Using NHANES 2001–2018 - Kamil, Alison; Wilson, Alissa R.; Rehm, Colin D. (Frontiers in Nutrition, 2021)
An agreed-upon measure of total dietary sweetness is lacking hindering assessments of population-level patterns and trends in dietary sweetness. This cross-sectional study used 24-hour dietary recall data for 74,461 participants age≥2y from nine cycles (2001-2018) of the National Health and Nutrition Examination Survey (NHANES) to evaluate trends in the sweetness of the diet in the United States. LCS-containing items were matched to a sugar-sweetened counterpart (e.g., diet cola-regular cola or sucralose-sugar). The matched pair was used to estimate the sugar equivalents from LCS sweetened foods/beverages to estimate dietary level sweetness, which was described as grams of approximate sugar equivalent (ASE) per day. Trends in ASE were estimated overall and by sub-group and trends were further disaggregated by food/beverage category. Overall, LCS sources contributed about 10.5% of ASE. Total ASE declined from 152 g/d to 117 g/d from 2001/2-2017/18 (p-trend<0.001), with comparable declines in children and adults. Declines in total ASE were predominantly driven by beverages (-36.7% from 2001/2-2017/18) and tabletop sweeteners (-23.8%), but not food (-1.5%). Observed trends were robust to sensitivity analyses incorporating random, systematic and sensory-trial informed estimates of sweetness as well as an analysis excluding possible under-reporters of dietary energy. This practical approach and underlying data may help researchers apply the technique to other dietary studies to further these questions.